A modular fabrication process for thin-film lithium niobate modulators with silicon photonics. (1st April 2022) - Mere, Viphretuo; Valdez, Forrest; Wang, Xiaoxi; Mookherjea, Shayan
Abstract: We report advancements in the fabrication of electro-optic Mach-Zehnder modulators made by bonding an unetched thin film of lithium niobate (LN) to a second chip with rib waveguides in another material, such as silicon. Devices were fabricated after storing bonded silicon-LN chips in a common laboratory environment for more than three years. The chips survived the full processing flow and yielded modulators with greater than 50 GHz 3 dB electro-optic bandwidth, and V π L less than 3 V cm at 1550 nm and equivalent performance to freshly-bonded and processed chips. Furthermore, we demonstrate the co-integration of hybrid bonded thin-film LN modulators and silicon photonics based high quality-factor ring resonators and higher-order coupled microring optical filters. The silicon microring resonators are used for photon-pair generation at 1550 nm using spontaneous four-wave mixing. These results show the feasibility of a modular modulator fabrication procedure, where the planarization and bonding steps are performed for a batch of chips at one time and smaller sub-batches are customized by end users at a much later time according to their needs and convenience.